2017
DOI: 10.1007/s00424-016-1930-6
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cell modulation of pyeloureteric peristalsis in the mouse renal pelvis examined using FIBSEM tomography and calcium indicators

Abstract: Typical and atypical smooth muscle cells (TSMCs and ASMCs, respectively) and interstitial cells (ICs) within the pacemaker region of the mouse renal pelvis were examined using focused ion beam scanning electron (FIB SEM) tomography, immunohistochemistry and Ca imaging. Individual cells within 500-900 electron micrograph stacks were volume rendered and associations with their neighbours established. 'Ribbon-shaped', Ano1 Cl channel immuno-reactive ICs were present in the adventitia and the sub-urothelial space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 34 publications
5
34
0
Order By: Relevance
“…In our previous study, intensely GFP-fluorescent PDGFRα (+) cells were located in both the adventitia and the suburothelial spaces in low magnified micrographs of the proximal renal pelvis, while the coexpression of α-smooth muscle actin in intensely fluorescent PDGFRα (+) cells was not evident. 8 In the present study, lightly GFP fluorescent PDGFRα (+) cells are densely distributed in the renal calyces and developed high-frequency spontaneous Ca 2+ transients. The morphological appearance of these lightly GFP fluorescent PDGFRα (+) cells, the properties of their spontaneous Ca 2+ transients, as well as their robust ATII-induced Ca 2+ response strongly suggested that they are the same population of cells as ASMCs, which are sparsely endowed with the α-smooth muscle actin and thought to be the pacemaker cells that electrically drive typical smooth muscle cells (TSMCs) to generate pyeloureteric peristalsis.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…In our previous study, intensely GFP-fluorescent PDGFRα (+) cells were located in both the adventitia and the suburothelial spaces in low magnified micrographs of the proximal renal pelvis, while the coexpression of α-smooth muscle actin in intensely fluorescent PDGFRα (+) cells was not evident. 8 In the present study, lightly GFP fluorescent PDGFRα (+) cells are densely distributed in the renal calyces and developed high-frequency spontaneous Ca 2+ transients. The morphological appearance of these lightly GFP fluorescent PDGFRα (+) cells, the properties of their spontaneous Ca 2+ transients, as well as their robust ATII-induced Ca 2+ response strongly suggested that they are the same population of cells as ASMCs, which are sparsely endowed with the α-smooth muscle actin and thought to be the pacemaker cells that electrically drive typical smooth muscle cells (TSMCs) to generate pyeloureteric peristalsis.…”
Section: Discussionsupporting
confidence: 50%
“…Distributions of the amplitude (0.43 ± 0.15 ΔF t /F 0 ), half width (624.9 ± 109.4 ms) and frequency (13.8 ± 4.2 minutes −1 , n =30, N = 21) of spontaneous Ca 2+ transients in this lightly fluorescent PDGFRα (+) cells ( Figure 2G) are very similar to that described for ASMCs. 8 Besides the predominant population of muscular PDGFRα (+) cells, intensely fluorescent PDGFRα (+) cells that had a round or oval shape GFP-expressing nuclei occasionally developed, slow, prolonged spontaneous Ca 2+ transients (Figure 2H,I; Supplement Movie S3). In seven PDGFRα (+) cells (n = 4, N = 3), spontaneous Ca 2+ transients had amplitudes of 0.98 ± 0.24 ΔF t /F 0 , the half-width of 2155.7 ± 655 ms) and frequency of 0.68 ± 0.36 minutes −1 .…”
Section: Ca 2+ Signaling In Pdgfrα (+) Cells Of the Proximal Renal mentioning
confidence: 98%
See 3 more Smart Citations